Dismantling the Center from the Margins : Patriarchy and Transnational Literature by Women - Conwell, Joan (East Carolina University, 2011)
This thesis explores the idea that transnational women writers are liminal figures: marginal as women, marginal as writers, and marginal as transnational personae "betwixt and between" nations. Authorial liminality provides a vantage point that is neither fully inside nor fully outside the system, and therefore privileges intimate literary confrontations with patriarchy. Beginning with a general discussion of transnational women writers, otherness, and liminality, the thesis progresses to more specific tropes--border crossing, Third Space, the subversive use of religious imagery and symbol, and the interplay between silence and voice--identified as anti-patriarchal devices in the works of contemporary transnational women writers. Chimamanda Ngozi Adichie's Purple Hibiscus, Elif Shafak's The Bastard of Istanbul, Edwidge Danticat's The Dew Breaker, and Fadia Faqir's Pillars of Salt are discussed as novels emblematic of anti-patriarchal fiction by contemporary transnational women writers, and the thesis explores the four tropes in the context of these works.
Keywords: Literature; Women's studies; Comparative literature; Liminality; Patriarchy; Silence; Space; Transnational literature; Women; Purple hibiscus; Bastard of Istanbul, The; Dew breaker, The; Pillars of salt; Patriarchy in literature; Women authors; Literature and transnationalism; Transnationalism; Adichie, Chimamanda Ngozi, 1977- . Purple hibiscus; Shafak, Elif, 1971- . Bastard of Istanbul; Danticat, Edwidge, 1969- . Dew breaker; Faqir, Fadia, 1956- . Pillars of salt